Workshop For Civil Servants Desa Duyung And Desa Grogol To Realize Digital Archive Management System - Fierda Nurany; Bagus Ananda Kurniawan; Muhammad Fadeli; Laili Dwi Agustina; Safira Firdaus (REKA ELKOMIKA: Jurnal Pengabdian kepada Masyarakat, 2023)
The objectives of this study are to analyze and examine the governance of village digital archives in the modernization era. The community service team from UBHARA has conducted digital archive development in Duyung Village and Grogol Village, aiming at facilitating easy public access to the existing government services. The community service methodwas in form of offline activities starting from preparation, coordination, implementation and evaluation. The results of the activity showed that the UBHARA community service team has successfully developed Google Form and Bit.ly for the Application for Making Letters in Duyung Village and Grogol Village Population Data. Thus, this demonstrates the importance ofgood understanding of digital archive management by utilizing the appropriate tools to enhance the efficiency of village archive management.